(untitled) (Nordic Journal of African Studies, 2008)
African tales of animals, humans, fantastic beings, villains and heroes are, much like their counterparts elsewhere, created for the entertainment of an audience of children. At a more implicit level, on the other hand, the same stories also portray and thoughtfully reflect on human nature. They comment on the moral strengths and weaknesses of human beings, they praise their solidarity and expose their differences and divisions. Opposition, strife and rivalry feature commonly in the realm of story telling. They form the focus of this essay and their discussion is derived from the analysis of four selected monographs, supplemented by over a hundred narratives collected by the author in the late nineties. From the monographs, which represent almost a century of research in the field of African folklore studies, emerge different perspectives on the subject of social discord. These are briefly defined. Subsequently, the paradigmatic horizons against which they arose, are identified. The remaining sections of the essay explore the wider cultural and social contexts of storytelling. It is suggested that the conflict theme is best explained in terms of the close affinity between the realm of storytelling on the one hand and the ritual pedagogy of initiation on the other. Furthermore, the theme of social discord, it is proposed, should be read as social commentary, rather than as being expressive of a spirit of rebellion against those who wield social power. The realm of children’s narratives, generally, seems supportive of the socio-political status quo, rather than subversive.